An Analysis of Gesture Used by English teacher in English Teaching and Learning Activity of the Eight Grade Students of SMP N 2 Sawan in Academic year 2015/2016 - ., I Kadek Supriawan Adinatha; ., Prof. Dr.I Nyoman Adi Jaya Putra, MA; ., Ni Wayan Surya Mahayanti, S.Pd, M.Pd (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Abstrak Penelitian ini bertujuan untuk mengetahui jenis-jenis gerakan dan fungsi gerakan tertentu dalam mengajar dan aktivitas belajar, terutama dalam tiga kegiatan domain, mereka adalah: kegiatan menyapa, kegiatan mengajar dan kegiatan Tanya jawab. Penelitian ini dilakukan di SMPN 2 Sawan. Penelitian ini adalah desain dengan menggunakan pendekatan deskriptif kualitatif dimana data yang terkumpul dianalisis secara kualitatif. Ada enam instrumen untuk mengumpulkan data, mereka adalah: catatan lapangan, kamera, checklist pengamatan, pedoman wawancara, handphone dan peralatan menulis. Peneliti melakukan penelitian ini sampai studi jenuh atau tidak ada perubahan dari gerakan yang digunakan oleh guru bahasa Inggris. Teori didukung oleh gerakan guru bahasa Inggris yang digunakan di dalam kelas maka peneliti juga ingin mengetahui jenis gerakan dalam tiga kegiatan dan fungsi gesture tertentu dalam tiga kegiatan. Kata Kunci : Kata kunci : gerakan dan aktivitas belajar mengajar Bahasa inggris Abstract This study was aimed at finding out the kinds of gestures and the functions of certain gestures in teaching and learning activity, especially in three domain activities, those were: greeting, delivering and asking & answering activities. This study was conducted at SMPN 2 Sawan. This study was design by using qualitative descriptive approach in which the data collected were analyzed qualitatively. There were six instrument to collect the data, those were: field notes, camera, observation checklist, guidance interview, hand phone and writing equipment. The researcher conducted this study until the study stuck or there was no change of the gesture used by English teacher. The data were transcribed and analyzed to find out the kinds of gestures and the function of certain gestures. Based on the theory from McNeil (2005) there were four types of gesture, and each types had kind gestures. The theory supported by English teacher gestures used in the classroom then the researcher also wanted to find out the kind of gesture in three activities and function of certain gesture in three activities. keyword : Keywords: Gesture, English teaching and learning activities